A Comparative study on Educational philosophies of Japan and Malaysian School Education System. - BG, Darsana (Journal of Neonatal Surgery, 2025)
The purpose of the study was to investigate the reflections on educational policies in Japan and Malaysia comparatively with regard to educational philosophies in school education. In this study a qualitative descriptive research was used to compare educational philosophies such as epistemology, axiology, concept of education, learner perspectives and knowledge aims related to creativity, innovation, skills and competencies of the two countries in their respective educational policies. The data were collected through document analysis. Content analysis was used to analyse qualitative data gathered from the official documents and research reports. Regarding the reflections of educational philosophies of policies, it was found that ultimate aim for knowledge acquisition is for overall development of the individual and the philosophy of education is thus concerned not only with philosophical questions about education as such but with larger questions of education policy and the roles of educational institutions in societies. It also reflect around the nature of education and the kinds of normative questions that arise concerning education for similar purposes in the two countries.